2001
DOI: 10.1046/j.1440-1746.2001.02629.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and histogenesis of colorectal Paneth cell metaplasia in idiopathic inflammatory bowel disease

Abstract: Paneth cell metaplasia is a non-specific phenomenon in the proximal colon, but distal PCM, which occurs exclusively in affected mucosa, is a useful marker indicating IBD, even in the inactive phase. Regression analysis suggests that repair and regeneration may be the most potent stimuli causing PCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 36 publications
(37 reference statements)
3
76
0
2
Order By: Relevance
“…30 It is more frequently observed at the ascending colon and cecum than at distal sites of elderly individuals and in affected mucosa than in healthy mucosa in patients with inflammatory bowel diseases. 16 Nevertheless, our results indicate that the presence of chronic active colitis with granuloma and/or Paneth cell metaplasia is not a specific feature of CCS. Prospective studies of the larger numbers of patients including, particularly, CBT patients are required to evaluate the incidence of chronic active colitis with granuloma and/or Paneth cell metaplasia in CCS, GVHD and other infectious colitis.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…30 It is more frequently observed at the ascending colon and cecum than at distal sites of elderly individuals and in affected mucosa than in healthy mucosa in patients with inflammatory bowel diseases. 16 Nevertheless, our results indicate that the presence of chronic active colitis with granuloma and/or Paneth cell metaplasia is not a specific feature of CCS. Prospective studies of the larger numbers of patients including, particularly, CBT patients are required to evaluate the incidence of chronic active colitis with granuloma and/or Paneth cell metaplasia in CCS, GVHD and other infectious colitis.…”
Section: Resultsmentioning
confidence: 53%
“…16,18 Paneth cells regulate the composition of colonized microbes in the intestine and protect epithelial cells from bacterial invasion. 19,20 We recently demonstrated that Paneth cells are targeted by GVHD, resulting in a subsequent alteration in the intestinal flora.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the NOD2/CARD15 gene is mainly expressed in Paneth cells, constitutively present in jejunum and ileum but also in the colon, mostly as metaplastic cells 18 . In these cells mutation of the NOD2/CARD15 gene reduces the expression of α-defensins, confirming its role in innate immunity 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found significant upregulation of lysozyme in actively inflamed colonic epithelium in CD and UC, which is consistent with the characteristic finding of colonic Paneth cell metaplasia in IBD. 8 Despite the above, we must point out that the scope of this study is limited. Due to the complex and time-consuming laser microdissection process we waived the analysis of noninflamed colon tissue of CD patients.…”
Section: Discussionmentioning
confidence: 95%